Pengaruh Kepercayaan Konsumen dan Harga Produk yang Dimediasi e-WOM terhadap Keputusan Pembelian di Platform Shopee - Ninggar Agustina Cindya Putri; Siska Hadiyanti; Andriya Risdwiyanto; Sabilla Saberina (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This study aims to analyze the influence of consumer trust and product price, mediated by e-WOM (electronic word-of-mouth), on purchase decisions on the Shopee platform. A quantitative approach was used, with a sample of 75 undergraduate students living in boarding houses in the Special Region of Yogyakarta who shop on Shopee. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS version 4. The results show that consumer trust and product price have a significant positive influence on purchase decisions, both directly and indirectly through e-WOM. This confirms the vital role of user reviews and recommendations in the decision-making process. The study provides strategic implications for e-commerce platforms and guidance for consumers. In addition, this study also provides guidance for consumers in considering factors that influence purchasing decisions on online platforms and educate them to be more careful in assessing available information before making a purchase. Overall, the results of this study underscore the important role of consumer trust, product price, and e-WOM in shaping purchasing decisions on e-commerce platforms.